Violência escolar : um breve estudo de casos na E.M.E. F Martins Monteiro Zona Rural do município de Novo Repartimento/PA - ARAUJO, Jociano Barbosa (2019)
This study aimed to make a case study on school violence in the Martins Monteiro Municipal Elementary School located in the Rural District of the municipality of Novo Repartimento-PA. It was an investigative study, because it sought to describe clearly the relationships that contribute to this problem and at the same time to investigate the practices taken by teachers and management that aim to combat violence in the teaching environment. The research was carried out in this school and the subjects surveyed were in the whole 28 people, being, being 7 teachers and 21 students of a multisseriado class of 8º and 9º of Elementary School. The method used was descriptive qualitative, from questionnaires with open and closed objective questions. It was verified that, just as the teachers studied present numerous difficulties to prevent as well as to combat school violence, students also experience great difficulties because of their being generally the victims and at the same time the cause of this problem. Faced with this, it is necessary to rethink the way schools and their professionals have dealt with school violence, so it is necessary to create partnerships involving security organs such as guardianship council, juvenile court, criminal court and the entire school community. The process of preventing and combating school violence may seem time-consuming, but it is necessary, as we have already seen, interferes directly in the process of teaching students' learning.